Land Warfare During the Russian-Ukrainian War and International Humanitarian Law - Kaźmierczak, Krzysztof (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The Russo-Ukrainian War is one of the largest – and probably the most intensive – conflicts of the last several decades. Fought between large, regular, and well-equipped forces of two sides, it naturally provides an extremely wide scope of materials for analysis as to the functioning of ius in bello. At the current stage, however, the evidence is often piecemeal and unclear, particularly taking into consideration the lack of access to documents and to Russian materials. While there is a significant body of evidence to indicate serious violations of humanitarian law, including indiscriminate or deliberate attacks on civilian targets, a detailed analysis requires taking into consideration a broader scope of circumstances which at this point are unclear. One of areas where we have strong evidence, if based on a sample, is the issue of the treatment of the prisoners of war. In general, the initial information seems to indicate widespread and systematic violations of humanitarian law during the conflict.